Balancing economic and social results in football clubs: evidence of fans’ perceptions in the Colombian context - Juan Alejandro Hernández-Hernández; Abraham Londoño-Pineda; Robert Ng-Henao; Juan Lucas Macías-Franco; Jose Alejandro Cano (Frontiers in Sports and Active Living)
Fans are not only loyal, but also powerful, and could therefore exert pressure on football club managers. This study examines the influence of fan-generated pressure on the economic and social sustainability outcomes of football clubs in Colombia, highlighting the role of active and non-active fan typologies. Using a conceptual framework rooted in stakeholder theory, we developed and tested a structural equation model (SEM) based on Colombian football fans. Results show that active fans, defined as direct or indirect followers, prioritize high-performing players and coaches and significantly influence economic outcomes through merchandising and broadcasting rights. Conversely, non-active fans, including passive and potential supporters, emphasize player stability and club goodwill. These findings highlight that fan pressure, shaped by sporting identity and performance expectations, serves as a critical lever for value co-creation and sustainability.